2012
DOI: 10.1038/ja.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Time-series analysis of the relationship of antimicrobial use and hand hygiene promotion with the incidence of healthcare-associated infections

Abstract: We analyzed the effect of antimicrobial use and implementation of a hand hygiene program on the incidence of healthcareassociated infections (HAIs) and healthcare-associated methicillin-resistant Staphylococcus aureus (HA-MRSA) infections at the Chung Shan Medical University Hospital (Taichung, Taiwan). Monthly data were retrospectively reviewed from January 2004 to December 2010. Use of antimicrobials and alcohol-based hand cleaner were separately regressed against the incidences of HAIs and HA-MRSA infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Of 3639 studies screened, 142 studies met initial inclusion criteria and 41 of these met EPOC criteria. Among these 41 studies, six were randomised controlled trials (including three cluster randomised controlled trials),31 32 33 34 35 36 32 were interrupted time series,28 29 30 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 one was a non-randomised trial,66 and two were controlled before-after studies 6768 Appendix 5 give details of the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 3639 studies screened, 142 studies met initial inclusion criteria and 41 of these met EPOC criteria. Among these 41 studies, six were randomised controlled trials (including three cluster randomised controlled trials),31 32 33 34 35 36 32 were interrupted time series,28 29 30 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 one was a non-randomised trial,66 and two were controlled before-after studies 6768 Appendix 5 give details of the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical outcomes were reported in 19 studies 2829 30 35 42 46 47 48 49 52 55 56 57 59 62 63 66 67 69 Appendix 6 provides full study characteristics including study design, setting, intervention, and comparison groups.…”
Section: Resultsmentioning
confidence: 99%
“…We are aware that strategies to combat the spread of these microorganisms are more complex and comprehensive, but hand hygiene remains a cornerstone. Patient education was included in only one study (22); the role of patients and the civil society in combating AMR is crucial at different levels and hand hygiene is one simple yet key measure that can be practiced and advocated for by them.…”
Section: Gaps and Research Perspectivesmentioning
confidence: 99%
“…It has been shown that more than 32% of HAI are avoidable [6,7] through hand washing and proper disinfection of medical devices between patients. The hands of healthcare professionals are the main vehicle for the transmission of microbes [3,8], but it is known that also contaminated medical devices (stethoscopes, otoscopes, and thermometers) can transmit microorganisms to patients [1, 2,5]. In particular, stethoscopes, which are considered the symbol of medicine, are widely used medical devices but, if they are not disinfected, they can cause cross-contamination [9,10].…”
Section: Introductionmentioning
confidence: 99%